Question Find the product to each problem (2x – 4y)(x + 3y) = (x − 4)(2x − 1) = (2x – 3)(x – 1) = (3x – 3y)(2x – y) =

Answer: Step-by-step explanation: To find the product of each expression, we can use the distributive property to expand the terms: (2x – 4y)(x + 3y) = 2xx + 2x3y – 4yx – 4y3y = 2x^2 + 6xy – 4xy – 12y^2 = 2x^2 – (-2xy – 12y^2) = 2x^2 – 2xy – 12y^2 (x − 4)(2x − 1) = x2x + x(-1) – 42x – 4(-1) = 2x^2 – x – 8x + 4 = 2x^2 – 9x + 4 (2x – 3)(x – 1) = 2xx + 2x(-1) – 3x – 3(-1) = 2x^2 – x – 3x + 3 = 2x^2 – 4x + 3 (3x – 3y)(2x – y) = 3x2x + 3x(-y) – 3y2x – 3y(-y) = 6x^2 – 3xy – 6xy – 3y^2 = 6x^2 – (-6xy – 3y^2) = 6x^2 – 6xy – 3y^2 I hope this helps! Let me know if you have any questions. Reply

Answer:Step-by-step explanation: